2003
DOI: 10.3346/jkms.2003.18.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Gabapentin in Rats

Abstract: Gabapentin has been known to elicit the antinociceptive effect. However, little has been known about the effect of gabapentin on the cardiovascular system. The author's aim of this experiment was to examine the hemodynamic effects of gabapentin. Male Sprague-Dawley rats were used. Intrathecal or intracerebroventricular catheters were implanted and gabapentin was delivered through each catheter or directly into the peritoneal cavity. For hemodynamic measurements, catheters were inserted into the tail artery. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In our study we found that gabapentin lead to more stabilization of heart rate and mean arterial blood pressure which was an index for pain reduction. while Myung et al found that in rats intrathecal and intraperitoneal gabapentin did not induce significant changes of hemodynamics over the 60 min compared to the baseline value [20]. Mausumi et al found that gabapentin provide hemodynamic stability during laparoscopic surgery in both sexes and this compatible with our study [21].…”
Section: Discussionsupporting
confidence: 81%
“…In our study we found that gabapentin lead to more stabilization of heart rate and mean arterial blood pressure which was an index for pain reduction. while Myung et al found that in rats intrathecal and intraperitoneal gabapentin did not induce significant changes of hemodynamics over the 60 min compared to the baseline value [20]. Mausumi et al found that gabapentin provide hemodynamic stability during laparoscopic surgery in both sexes and this compatible with our study [21].…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study, gabapentin administered at doses of 10, 30, 100 and 300 mg/kg intraperitoneally to Sprague -Dawley rats had no effect on BP or heart rate postadministration. 21 A possible explanation for the lack of any clinically relevant effect of gabapentin on isoflurane MAC might be Table 1 Arterial acid -base and blood gas data, and cardiovascular parameters at baseline and following intraperitoneal saline and gabapentin (30-1000 mg/kg) administration that gabapentin is primarily an analgesic for persistent inflammatory and/or neuropathic pain associated with hyperalgesia 5 and not against acute noxious stimuli such as a tail clamp as was applied in our experiments. Human studies investigating the reduction of perioperative pain or opioid consumption upon the administration of gabapentin have been inconsistent.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, i.p. administration of gabapentin at doses up to 300 mg/kg in rat did not affect heart rate and blood pressure [68]. For spinal drug administration, 5 µl of saline or gabapentin (200 µg/5 µl) [20; 68] were injected slowly via the intrathecal catheter, followed by a 1 µl air bubble and 9 µl saline flush.…”
Section: Methodsmentioning
confidence: 99%